Digital chromatic dispersion pre-management for SSB modulation direct-detection optical transmission systems - Zhong, Xiaoyu (2019)
Recently, single-side-band (SSB) modulation direct detection (DD) based optical transmission systems have attracted great interest due to their capability of electronic chromatic dispersion (CD) compensation. In this paper, we investigate the digital chromatic dispersion pre-management for optical SSB signals which are generated by radio frequency (RF) tone based on I/Q modulator and optical carrier based dual-drive Mach–Zehnder modulator (DDMZM) with DD at the C-band via numerical simulations. The impact of CD, self-phase modulation (SPM) and phase-to-amplitude noise on such a SSB DD optical transmission system with I/Q modulator based virtual carrier assisted, and the DDMZM based optical carrier are investigated. The simulation results have successfully demonstrated the transmission of a 224-Gb/s Nyquist 16-ary quadrature amplitude modulation (16QAM) signal over 75-km standard single mode fiber (SSMF) with bit error rate (BER) less than 3.8 10−3 in a SSB-DD system by using digital CD pre-management. It is shown that the SPM induced impairment can be optically mitigated by the residual positive CD of the SSMF link.